Socialization and media consumption in a Primary Education classroom (Asturias, Spain): A qualitative approach in process - Buelga Iglesias, María; Calvo González, Soraya (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Media consumption through different social networks is part of adolescent digital culture. This article aims to describe the qualitative methodological proposal designed to analyse the influences of Relationship, Information and Communication Technologies on a group of children in Primary Education from a gender perspective. An ethnographic approach is used, and different data collection techniques are applied, such as participant observation, assemblies or experimentation and media creation sessions. Finally, guessworks are offered as an exploratory review of the fieldwork.